Spawning modern fish : transnational comparison in the making of Japanese salmon - Swanson, Heather Anne, 1979- (Culture, place, and nature., 2022)
"Since the mid-nineteenth century, agricultural development and fisheries management in northern Japan have been profoundly shaped by how people within and beyond Japan have compared Hokkaido's landscapes to those of other places, as part of efforts to make the new Japanese nation-state more legibly "modern." In doing so, they engaged in heterodox modes of analogic thinking that reached out to diverse places, including the American West and southern Chile. Today, the comparisons made by Hokkaido fishing industry professionals, scientists, and Ainu indigenous groups between the island's forests, fields, and waters and those of others around the world continue to dramatically affect the region's approaches to environmental management and its physical landscapes. In this far-ranging ethnography, Heather Swanson shows how this traffic shapes the course of Hokkaido's development, its fish, and the lives of people on and beyond the island. Resulting encounters restructure not only trade dynamics and political economy but also multispecies relations in watersheds around the globe"--